2003
DOI: 10.1073/pnas.0630614100
|View full text |Cite
|
Sign up to set email alerts
|

Induction of bilirubin clearance by the constitutive androstane receptor (CAR)

Abstract: Bilirubin clearance is one of the numerous important functions of the liver. Defects in this process result in jaundice, which is particularly common in neonates. Elevated bilirubin levels can be decreased by treatment with phenobarbital. Because the nuclear hormone receptor constitutive androstane receptor (CAR) mediates hepatic effects of this xenobiotic inducer, we hypothesized that CAR could be a regulator of bilirubin clearance. Activation of the nuclear hormone receptor CAR increases hepatic expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
269
1
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(283 citation statements)
references
References 46 publications
11
269
1
2
Order By: Relevance
“…Both receptors protect the body from the deleterious accumulation of bilirubin [61,62] and bile acids [63] through hepatic induction of several enzyme genes. Additionally, many CAR and PXR target genes, including CYP3A and CYP2B, are involved in steroid hormone metabolism and their induction could contribute to the endocrine disruption activities of drugs and contaminants [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors protect the body from the deleterious accumulation of bilirubin [61,62] and bile acids [63] through hepatic induction of several enzyme genes. Additionally, many CAR and PXR target genes, including CYP3A and CYP2B, are involved in steroid hormone metabolism and their induction could contribute to the endocrine disruption activities of drugs and contaminants [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, activation of both PXR and CAR increases clearance of bilirubin from hepatocytes [42,57]. Bilirubin does not directly bind to either CAR or PXR [57]. Instead, bilirubin activates CAR indirectly by promoting cytoplasmic-nuclear translocation, similar to the effects described for phenobarbital on CAR [57].…”
mentioning
confidence: 85%
“…Studies using CAR-defective mice demonstrated that all proteins involved in bilirubin clearance by hepatocytes are under the control of CAR including OATP1B1 and 1B3 (uptake transporters for bilirubin and bilirubin monoglucuronide into hepatocytes), GSTA1/2 (involved in intracellular binding of bilirubin), bilirubin conjugating UGT1A1 and Mrp2 (responsible for biliary secretion of bilirubin conjugates [78]. Low CAR expression in the fetus may contribute to neonatal jaundice [78].…”
Section: Possible Autoregulatory Control Of Ugt1a1 By Bilirubinmentioning
confidence: 99%
“…Low CAR expression in the fetus may contribute to neonatal jaundice [78]. Bilirubin is the toxic end product of heme catabolism.…”
Section: Possible Autoregulatory Control Of Ugt1a1 By Bilirubinmentioning
confidence: 99%
See 1 more Smart Citation